Examining The Time Prisoners Study Using E-Learning While In Prison: Sustainability of E-Learning Programs in Prison - Mahlangu Vimbi Petrus (Discourse and Communication for Sustainable Education)
This study investigates the amount of time that convicts dedicate to studying through e-learning while in jail, with the goal of comprehending their drive despite difficult living conditions. The qualitative research was carried out at a jail in Namibia, using interviews as the method of data collection, in accordance with an interpretive paradigm. Thematic analysis was conducted on verbatim transcriptions of tape-recorded interviews. Namibia’s judicial system has shifted its focus from punitive measures to prioritizing prisons and community reintegration. Prisoners exhibit a resolute commitment to furthering their education using e-learning programs, regardless of the constraints imposed by their surroundings. Through the adoption of e-learning opportunities, inmates are given the ability to overcome obstacles to education that are typically linked to being incarcerated, such as having limited access to educational resources and restricted study hours. E-learning platforms offer jailed individuals a flexible and easily accessible method of acquiring knowledge and skills, enabling them to pursue academic interests and career goals. Furthermore, the results indicate that e-learning programs have the capacity to foster optimism and a sense of direction among incarcerated individuals, providing them with a means to rehabilitate and reintegrate into society effectively after their release. Through participation in educational endeavors, jailed prisoners not only obtain academic credentials but also cultivate important life skills and competencies that are crucial for their reintegration into society.